Learning Implementation System of Sewing Course at Course and Training Institute (LKP) Ratu Mode Pekanbaru City - Yuka Martlisda Anwika; Ihat Hatimah; Yanti Shantini (Jurnal Penelitian Pendidikan IPA, 2025)
The study aims to obtain information about Learning Implementation System of Sewing Course at Course and Training Institute (LKP) Ratu Mode Pekanbaru City. The study used a descriptive qualitative approach. The results of the study are participants of all ages, the curriculum refers to the SKKNI curriculum standards, facilities and infrastructure supporting sewing course learning are available. Partnerships include the Pekanbaru City Education Office, the Provincial Education Office, supervisors, PT, PAUD PNF, SMK and others. Course and Training Center (LKP) Ratu Mode also partners with industry, garment factories and other private companies in the clothing sector. The learning process uses 20% theory and 80% practice. As a result, participants have professional and good knowledge, skills, attitudes and characters in work and entrepreneurship. The management actively directs and provides information on job opportunities in the industrial and garment sectors. The impact is that some students have opened independent sewing businesses, helped teach others, opened sewing business groups together and have new jobs sewing in garment factories, industry, clothing sectors and so on